COVID-19 attitudes among social media users in Greece - Gemenis, Kostas (My University, 2021)
The dataset contains responses from two web surveys (fieldwork: 1-8 April and 13-20 May 2020 respectively) in Greece. The participants were invited to complete the survey via announcements and advertisements on social media. The surveys included questions taken from the European Social Survey, as well as batteries of questions on attitudes related to the COVID-19 pandemic, political knowledge, and health literacy. The dataset includes entropy balancing weights calculated using a reference sample from a nationally representative telephone survey.
Keywords: Health and Life Sciences; Social Sciences; Medicine